The ASIC3/P2X3 cognate receptor is a pain-relevant and ligand-gated cationic channel - Gabriele Stephan (Nature Portfolio, 2018)
Two subclasses of ligand-gated ion channels (ASIC3 and P2X3) are both present at sensory neurons and might be therefore subject to receptor crosstalk. Here authors use electrophysiology, biochemistry and co-immunoprecipitation to show that the two ion channels interact and affect P2X3 currents.